Pomegranate-like Ni-doped cobalt boride implanted in B, N-doped carbon nanocages for enhanced electrochemical oxygen evolution. (29th May 2023) - Ding, Junxia; Zhu, Xiaolun; Pei, Hebing; He, Simin; Yang, Rui; Liu, Nijuan; Guo, Ruibin; Mo, Zunli
Abstract: The development of efficient and stable transition metal boride electrocatalysts for oxygen evolution reaction (OER) is critical for energy conversion and environmental protection. Herein, we synthesized B, N-doped carbon layer encapsulated the Ni-doped Cox B nanocages electrocatalyst (denoted as Ni-Cox B@BNC) via a high-temperature boronizing, derived from Ni-doped cobalt-based zeolite imidazole frame (NiCo-ZIF), toward enhanced electrochemical alkaline oxygen evolution reaction. The Ni-Cox B@BNC electrocatalyst synthesized at 550 °C exhibits excellent OER activity with a low overpotential of 274 mV and a Tafel slope of 80 mV dec −1 at a current density of 10 mA cm −2, which is better than precious metal RuO2 . The synergistic effect between B, N-doped carbon layer and Ni-doped Cox B in Ni-Cox B@BNC leads to higher OER catalytic activity. The B, N-doped carbon layer provides additional active sites, which accelerates charge transport and enhances the conductivity of Ni-Cox B@BNC during OER. In addition, it also protects the pomegranate seed-like Ni-Cox B nanoparticles inside, improving the stability of the Ni-Cox B@BNC material. This work unambiguously elucidates the design and preparation strategy of transition metal boride implanted B, N-doped carbon nanocage electrocatalysts derived from controlled bimetallic ZIF precursor. Graphical abstract: Image 1 Highlights: The pomegranate-like Ni-Cox B@BNC is synthesized as predicted precious-metal-free OER catalyst. NiCo-ZIF as a precursor provides Ni-Cox B@BNC with higher electrochemical area and porosity. Ni-Cox B@BNC is verified with a very low OER overpotential of 274 mV at 10 mA cm −2 . The B, N-doped carbon layer provides extra active sites and accelerates charge transport during OER.